Rehabilitation of the former nuclear test site at Maralinga. (1st June 2021) - Long, Stephen; Cook, Megan; Charalambous, Fiona; Carpenter, Julia
Abstract: Large areas of the former British nuclear test site at Maralinga were contaminated by the explosive dispersal of plutonium. The Australian Government, in consultation with stakeholders, determined that the site should be cleaned-up so that it is fit for unrestricted habitation by the Aboriginal traditional owners (Maralinga Tjarutja). Engagement with the stakeholders, particularly the Maralinga Tjarutja, determined that the specific criterion for rehabilitation was 5 mSv y −1 and that some restrictions on permanent occupancy should remain. Remediation of the site began in 1995, took 5 years and cost AU106 million. The site was returned to its traditional owners in 2009 and is now the site of a flourishing tourism operation.